Pengaruh Digital Marketing Melalui Instagram Dan Discount Seasonal Terhadap Impulsive Buying Pada Layanan Mcdelivery - Hidayat Rizky Pratama; Ratih Hadiantini; Sabilla Saberina (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
This study aims to see the state and influence of digital marketing through Instagram and seasonal discounts on impulsive purchases on McDelivery services. The data shows McDelivery is in third place with a proportion of 21% as the most frequently used fast food delivery, this is presumably due to promotional services carried out by McDelivery on Digital Marketing via Instagram, where McDelivery is only promoted on the official Instagram account @McDonaldsid which makes The promos on the McDelivery service are less focused because they integrate with other promos. The population in this study were all McDelivery Indonesia users with a total population of 17,609 which came from the number of McDelivery application downloads on the app store and play store with a sample size of 100 respondents. By using survey research methods, with descriptive and associative types of research that aims to determine the existence of independent variables and to determine whether the influence of the dependent variable on the independent variable. The results of the large trial of the effect of digital marketing (X1) on impulsive buying (Y) is 30.73%. The big influence of seasonal discount (X2) on impulsive buying (Y) is 20.76%. The effect of digital marketing (X1) and seasonal discounts (X2) on impulsive buying (Y) is 57.80%, of which 40.20% is outside research.